An account of the loss of the Country Ship Forbes and Frazer Sinclair, her late Commander - Liebner, Horst H.; van Dyke, David (UI Scholars Hub, 2016)
This paper reports on the life of the English Country trader Captain Frazer Sinclair leading up to and following the loss of the Forbes in the Karimata Strait in 1806. It examines the adventure and tenuous times of trading around the Indonesian archipelago after the fall of the VOC and subsequent transfer to the British. Included are the details of Captain Sinclair's trading history, multiple prizes as a privateer, and shipwrecks.